Host Rock Packaging in the Big Gossan - Kucing Liar Cu-Au Mineralization Type in the Grasberg-Ertsberg District, Papua - Herman Setyadi; Wahyu Sunyoto (Ikatan Ahli Geologi Indonesia, 2000)
The Grasberg-Ertsberg Mining District is located in the highlands of the central range Jayawijaya Mountains of Papua (Irian Jaya) province, Indonesia. The Grasberg-Ertsberg District is one of the richest mining districts in the world. The district contains six known skarn and porphyry copper deposits with mineable reserves. Total 1999 proven and probable reserves in the district are 2.5 billion tonnes at 1.13% Cu and 1.05 g/t Au, dominated by the Grasberg super-giant porphyry copper-gold deposit (1.9 bt @ 1.04% u, 1.04 g/t Au).Kucing Liar and Big Gossan deposits occur in the stratigraphy contact of New Guinea Group and Kembelangan Group. The other skarn system occurs associated with the contact of New Guinea group and Ertsberg Diorite. This paper presents a review of the copper-gold mineralization appears in the sedimentary units and/or stratigraphic controls and its potential around the Grasberg-Ertsberg district related to this mineralization type.